Protective effect of salidroside on streptozotocin-induced diabetic nephropathy by inhibiting oxidative stress and inflammation in rats via the Akt/GSK-3β signalling pathway - Delong Pei; Shengri Tian; Yanqiu Bao; Jun Zhang; Dongyuan Xu; Minhu Piao (Taylor & Francis Group, 2022)
Context Salidroside (SAL), one of the major glycosides isolated from the roots of Rhodiola rosea L. (Crassulaceae), has anti-inflammatory, antioxidant, and antidiabetic properties.Objective Our study assessed whether SAL exerts a protective effect on streptozotocin (STZ)-induced diabetic nephropathy (DN) in rats via the Akt/GSK-3β signalling pathway.Materials and methods Adult male Wistar rats were divided into three groups (n = 8): normal control, DN + vehicle, and DN + SAL. SAL (50 mg/kg/day, oral) was administered for 8 weeks. Biochemical and histopathologic examinations were performed to evaluate the therapeutic effects of SAL on oxidative stress, inflammation, renal function, and apoptosis.Results SAL induced rats demonstrated ameliorated levels of FBG (20.53 ± 0.72 mmol/L vs. 26.02 ± 1.44 mmol/L), urine albumin excretion (27.00 ± 1.46 mmol/L vs. 41.00 ± 1.59 mmol/L), blood urea nitrogen (14.42 ± 0.70 mmol/L vs. 17.77 ± 0.72 mmol/L), and serum creatinine (112.80 ± 6.98 mmol/L vs. 159.00 ± 3.81 mmol/L) compared to normal control rats, along with the alleviation of renal pathologic changes by improving the irregular shape of glomeruli tissues. Biochemical analysis showed that SAL-treated animals displayed suppressed levels of serum inflammatory cytokines and kidney oxidative stress markers and attenuated apoptotic characteristics. Moreover, it increased the phosphorylation levels of Akt and GSK-3β in kidneys.Discussion and conclusion The present study validated the involvement of the Akt/GSK-3β signalling pathway in renal improvement. These findings can form the basis to investigate the protective effect of SAL in DN in clinical trials.